China and India: A Tale of Two Trade Integration Approaches - Przemyslaw Kowalski (Indian Council for Research on International Economic Relations (ICRIER), 2008)
The comparison of the key features of trade integration processes and the economic outcomes in China and India reveals that while much has already been achieved in both these economies, the Chinese reforms, especially with respect to manufacturing trade, have gone further and that this is likely one of the key determinants of better economic performance of China. Still, China's integration process so far remains characterized by a certain duality. On the one hand the opening up of trade and FDI in manufactured goods has spurred the emergence of a largely private sector. On the other hand the high level of public ownership and important regulatory barriers continue to dominate the services sectors. India has gone a long way in reducing its tariffs on non-agricultural products as well as selected non-tariff barriers but moderate protection still persists which likely adds to the hurdles faced by the Indian manufacturing sector. India has revealed a comparative advantage in certain segments of the services sector but its services trade policy is still very restrictive, even as compared to China. More generally the extent of liberalisation achieved so far in India and the outcomes it brought about suggest that the remaining goods and services trade barriers are just but one item on the list of reforms that India needs to tackle in order to promote trade-led expansion of more labour-intensive activities.
Keywords: F13; F14; F15; F21; F23; F43; 330; China; India; manufacturing; services; trade barriers; trade policy; Internationale Wirtschaft; Außenwirtschaftspolitik; Auslandsinvestition; Wirtschaftswachstum; China; Indien